Combination of purple sweet potato (Ipomoea batatas L.) leaf extract with metformin on blood glucose and total cholesterol levels of albino rats induced by high-fat diet and streptozotocin - Saing, Marselina; Harahap, Urip; Sitorus, Panal (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to impaired insulin secretion, often accompanied by hypercholesterolemia. Metformin is a first-line antihyperglycemic drug that is often combined with other antihyperglycemic drugs. Purple sweet potato leaves have been widely studied to reduce glucose and cholesterol levels. Methods: This study was an experimental study using rats induced with a high-fat diet and streptozotocin, which were divided into 8 treatment groups, namely groups given CMC Na 0.5%, Metformin 45 mg/kg BW, Purple Sweet Potato Leaf Extract (SPLE) 200 mg/kg BW, SPLE 400 mg/kg BW, SPLE 800 mg/kg BW, SPLE 200 mg/kg BW with metformin 45 mg/kg BW, SPLE 400 mg/kg BW with metformin 45 mg/kg BW, and SPLE 800 mg/kg BW with metformin 45 mg/kg BW. Results: After treatment for 28 days with SPLE doses of 200 mg, 400 mg, and 800 mg/kg BW, both single doses and combinations with metformin showed a decrease in fasting blood glucose levels and total cholesterol, which were statistically significantly different (p<0.05) between treatment groups using the one-way ANOVA. The combination of SPLE 800 mg/kg BW with metformin normalized blood glucose levels of 93.50±4.93 mg/dl. Conclusion: The combination of purple sweet potato leaf extract with metformin is more effective in reducing blood glucose and total cholesterol levels compared to the single administration of metformin and SPLE.